2013
DOI: 10.1038/nrrheum.2013.147
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in the pathology and treatment of systemic lupus erythematosus

Abstract: Oxidative stress is increased in systemic lupus erythematosus (SLE), and it contributes to immune system dysregulation, abnormal activation and processing of cell-death signals, autoantibody production and fatal comorbidities. Mitochondrial dysfunction in T cells promotes the release of highly diffusible inflammatory lipid hydroperoxides, which spread oxidative stress to other intracellular organelles and through the bloodstream. Oxidative modification of self antigens triggers autoimmunity, and the degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
256
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 296 publications
(273 citation statements)
references
References 133 publications
(237 reference statements)
13
256
0
4
Order By: Relevance
“…SLE is an autoimmune inflammatory disease whose pathogenesis also refers to oxidative stress. Several studies have shown increased production of ROS or diminished levels of intracellular reduced glutathione in various blood components in SLE patients [11,12]. Several investigators suggested that restoration of the redox balance using antioxidant agents or diminishing effect of oxidative stress by intake of antioxidant nutrients, might attenuate the complication of SLE induced by oxidative stress [11].…”
Section: Oxidative Stress and Autoimmunitymentioning
confidence: 99%
See 1 more Smart Citation
“…SLE is an autoimmune inflammatory disease whose pathogenesis also refers to oxidative stress. Several studies have shown increased production of ROS or diminished levels of intracellular reduced glutathione in various blood components in SLE patients [11,12]. Several investigators suggested that restoration of the redox balance using antioxidant agents or diminishing effect of oxidative stress by intake of antioxidant nutrients, might attenuate the complication of SLE induced by oxidative stress [11].…”
Section: Oxidative Stress and Autoimmunitymentioning
confidence: 99%
“…Several studies have shown increased production of ROS or diminished levels of intracellular reduced glutathione in various blood components in SLE patients [11,12]. Several investigators suggested that restoration of the redox balance using antioxidant agents or diminishing effect of oxidative stress by intake of antioxidant nutrients, might attenuate the complication of SLE induced by oxidative stress [11]. Similarly, the deficiencies of SOD and peroxiredoxin inducing oxidative stress were considered to be an essential factor that might participate in the pathogenesis of another autoimmune disease autoimmune hemolytic anemia.…”
Section: Oxidative Stress and Autoimmunitymentioning
confidence: 99%
“…For example, in systemic lupus erythematosus, which is an autoimmune disease, it has been proposed that oxidative stress may play a role in pathogenesis as well as increase in the course of the disease (11). Similarly, oxidative stress has also been demonstrated to be high in systemic sclerosis, another autoimmune disease (12).…”
Section: Introductionmentioning
confidence: 99%
“…Increased oxidative stress has been amply documented in SLE (41). To a large degree it is secondary to the chronic inflammation that occurs during the course of disease progression and/or during active disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, diminished ROS production by phagocytic cells due to NADPH oxidase deficiency can cause impaired digestion of microbes or debris followed by increased Toll-like receptor stimulation (41) and/or altered redox status of cellular proteins resulting in increased proinflammatory cytokine production via the NFB pathway.…”
Section: Discussionmentioning
confidence: 99%